Methodology for the economic evaluation of CO2 derived materials. Issue 4 (20th October 2021) - Wong, Tiffany; Zilnik, Dan; Extavour, Marcius; Leitch, Michael
Abstract: Scoring the technologies in competition for the NRG Canada's Oil Sands Innovation Alliance Carbon XPRIZE required an economic evaluation to estimate the value created through the conversion of CO2 emissions into products. Across all of the Teams participating in the competition, 58 different materials were consumed and produced. Standardized prices and market sizes needed to be established for each of these materials to ensure a consistent evaluation across all Teams. The Standards Data Set (SDS) was created as a standardized database of economic data used in the competition. The rationale for the SDS project and the methodology for researching each material is described. Ultimately, credible material definitions using the SDS methodology were created for all materials, and some research and methodological customization were required for materials that did not have credible, publicly available market data. The methodologies for establishing credible values and market sizes for concrete, concrete admixtures and syngas are highlighted as examples of materials whose value and markets are not easily defined. Abstract : Scoring the technologies in competition for the NRG COSIA Carbon XPRIZE required an economic evaluation to estimate the value created through the conversion of CO2 into products. The methodologies for establishing credible values and market sizes for concrete, concrete admixtures and syngas are highlighted in this paper. Graphical Abstract: